2000
DOI: 10.1148/radiology.215.3.r00jn25761
|View full text |Cite
|
Sign up to set email alerts
|

Staging of Advanced Ovarian Cancer: Comparison of Imaging Modalities—Report from the Radiological Diagnostic Oncology Group

Abstract: CT and MR imaging are equally accurate, and either modality can be used to stage advanced ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
179
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(194 citation statements)
references
References 24 publications
7
179
0
8
Order By: Relevance
“…Some studies have found MRI to be more accurate in this regard, especially for lymph node metastases and tumor resectability. 77,78 Contrast-enhanced MRI have been found to have a 92% sensitivity in detecting small peritoneal disease such as those that can be found in the omentum, in the mesentery of the small and large bowel, on the anterior abdominal peritoneal surface, under the diaphragm, and in the paracolic gutters. 77 Prolonged survival after ovarian cancer diagnosis and the success of chemotherapy depends on optimal debulking at the time of the initial surgery, yet less than 50% of ovarian cancer patients acquire a gynecologic oncologist to be involved in their care.…”
Section: Gynecologic Malignanciesmentioning
confidence: 99%
“…Some studies have found MRI to be more accurate in this regard, especially for lymph node metastases and tumor resectability. 77,78 Contrast-enhanced MRI have been found to have a 92% sensitivity in detecting small peritoneal disease such as those that can be found in the omentum, in the mesentery of the small and large bowel, on the anterior abdominal peritoneal surface, under the diaphragm, and in the paracolic gutters. 77 Prolonged survival after ovarian cancer diagnosis and the success of chemotherapy depends on optimal debulking at the time of the initial surgery, yet less than 50% of ovarian cancer patients acquire a gynecologic oncologist to be involved in their care.…”
Section: Gynecologic Malignanciesmentioning
confidence: 99%
“…The maximum likelihood estimates of the segmentation quality parameters are: (6) In our experience, typically only K <20 iterations were required to achieve convergence in several segmentation applications.…”
Section: The Maximization (M) Stepmentioning
confidence: 99%
“…For example, a five-point scale might be adopted for observer performance evaluations, where 1 = definitely normal, 2 = probably normal, 3 = probably abnormal, 4 = probably abnormal, and 5 = definitely abnormal. A discrete subjective rating method was used in a multi-modal (magnetic resonance [MR], computed tomography [CT], and ultrasound) comparative ovarian cancer technology assessment study (5,6), in one of a series of prospective multicenter Radiologic Diagnostic Oncology Group clinical trials sponsored by the funded by the National Institutes of Health in the 1990s. The advantages of the continuous diagnostic over ordinal scale are that detailed information is preserved, they are more natural with the advancements in measurement tools and computing methods, and enable more objective interpretations.…”
mentioning
confidence: 99%
“…Recurrent EOC, unlike other solid tumors, tends to present without accompanying symptoms and forms multiple small implantations, particularly in the small intestine and mesentery, which cannot be readily detected using conventional imaging techniques (13,14).…”
Section: Introductionmentioning
confidence: 99%